2004
DOI: 10.1590/s0102-86502004000100010
|View full text |Cite
|
Sign up to set email alerts
|

Modelo animal de doença: critérios de escolha e espécies de animais de uso corrente

Abstract: OBJETIVO: Delinear os parâmetros que norteiam a escolha de um modelo animal de doença e verificar na literatura biomédica recente quais as espécies animais de uso mais freqüente. MÉTODOS: Considerando a revisão da literatura são discutidos, os conceitos e as características de um modelo animal de doença. Destaca-se o consenso atual sobre quando usar um modelo animal, quais os critérios de sua escolha e os requisitos para um modelo adequado. Descreve quais os tipos de modelos animal de doença e discute as contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
2
22

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 0 publications
0
50
2
22
Order By: Relevance
“…The size of the sample was defined based on studies already done to evaluate tadalafil in renal ischemia, with the aim of using as few animals as possible to demonstrate significant histological changes 16 .…”
Section: ■ Discussionmentioning
confidence: 99%
“…The size of the sample was defined based on studies already done to evaluate tadalafil in renal ischemia, with the aim of using as few animals as possible to demonstrate significant histological changes 16 .…”
Section: ■ Discussionmentioning
confidence: 99%
“…Animals models can be classified into: 1) spontaneous models, 2) experimental models, 3) genetically modified models, 4) orphan models, and 5) negative models 4,[9][10][11] . Spontaneous animals models are those that exist in the nature with similarity to human condition or disease.…”
Section: Animal Modelsmentioning
confidence: 99%
“…An effective animal model enables the investigation of spontaneous or induced pathological process and resembles the same phenomenon/disease in one or more aspects of the pathological process in humans 9 . The domestic pig is still widely used as an animal model for the study of human disease, and has been shown to be similar to man for biological, anatomic, physiological and nutritional characteristics 10 .…”
Section: Introductionmentioning
confidence: 99%